(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The text is about Jelica Belović Bernadzikowska, a writer, ethnographer and teacher, and about her work on self-affirmation and the affirmation of her contemporaries. Bernadzikowska’s effort to describe and present the work of Serbian women in the cultural domain is seen in the light of the specific notion of culture she uses in her monograph on textile art (1907) and connected to the work and reception of her contemporaries who were presented in the almanac Serbian Woman (1913).